Small Books with a Mission : Prayer Books as Tools of Re-Catholicisation, c. 1540–1590 - Norberg-Schiefauer, Fredrik (Bibliotheca historico-ecclesiastica Lundensis, 2025)
This thesis examines the role of German-language Catholic prayer books in the re-Catholicisation of Protestants during the approximate timeline 1540–1590. Within the broader context of the Catholic Reformation, these prayer books served as instruments of doctrinal transmission and devotional instruction, representing a form of ‘soft’ re-Catholicisation in contrast to the coercive methods used by secular authorities. By examining both catechetical meta-texts – such as prefaces, didactic introductions and marginal commentaries – as well as the prayers themselves, this study explores how these texts sought to persuade Protestants of the truth in Catholic doctrine and devotional practices. Through an analysis of key points of confessional controversy – including ecclesiology, sacramental theology, Mariology, prayers for the dead and various sacramentals – this study highlights the didactic and polemical dimensions of these prayer books. Furthermore, it demonstrates how these texts appealed to antiquity and tradition, as well as biblical and patristic authority, in order to counter Protestant critiques. In addition, it considers the language used in the prayer books, showing how theological concepts were articulated to reinforce Catholic doctrine and piety as well as confessional identity among the readers. This study situates Catholic prayer books within the theoretical framework of confessional knowledge and culture, thereby identifying the authors as ‘knowledge actors’ representing the Catholic Church as a ‘knowledge institution’. By aligning this study with scholarship on confessionalisation and devotional literature, it contributes to our understanding of how Catholic devotional texts contributed to developing a mono-confessional Catholic culture in early modern Europe. Furthermore, this thesis challenges previous assumptions that early modern devotional literature was non-polemical in nature, demonstrating that while Catholic prayer books were engaged in apologetics and catechesis, they also promoted a compassionate yet firm stance towards Protestants. Ultimately, this thesis advances the discussion on prayer books as mediators of doctrine and thus reveals their significant role in the transmission and internalisation of Catholic teachings during a critical period of confessional formation.
Keywords: re-Catholicisation; prayer books; devotional literature; devotional practices; confessional controversy; confessional culture; confessional knowledge; confessionalised literature; apologetics; polemic; persuasion; catechesis; Early Modern Catholicism; Protestantism; Reformation; Counter-Reformation; Holy Roman Empire; Jesuits